Order of Mention in Causal Sequences: Talking about Cause and Effect in Narratives and Warning Signs. Issue 8 (17th November 2019) - Kaiser, Elsi
ABSTRACT: Causal sequences can be segmented into cause and effect. However, some argue causal relations in discourse are by default in effect–cause order. Others claim cause–effect order is easier to process and the default way of expressing causality, due to iconicity. We conducted experiments testing participants' production choices in two different contexts—narratives and safety/warning signs—to see whether genres/discourse types differ in their preferred cause–effect order. We find that while narratives (which involve temporally anchored events) elicit iconic cause–effect order, safety signs (with generic statements rather than specific temporally anchored events) show a bias toward effect–cause. The present work highlights the importance of differences in text type and communicative purpose and suggests that there is no single answer regarding the primacy/salience of cause versus effect.